Рок-музика - Леушина, А. А. (ХНУРЕ, 2020)
This report examines the development of rock music. Сhanging styles and varieties of genre was examined with passage of time. The problem of the influence of rock music on politics and society was adressed. The emergence of so-called musical sub-cultures and their differences. Музика має велику силу, вона діє на людину навіть якщо він не помічає. З давніх часів церква використовує музику для поглиблення свого впливу на громадян. За допомогою маршів та гімнів закликали до битви. Матері співають своїм дітям колискові, щоб заспокоїти їх.
Keywords: Рок-музика; українознавство; традиції; культура